Vulnerabilidade natural no Sistema Aqüífero Guarani e análise de parâmetros físico-químicos das águas subterrâneas em Quaraí, BR e Artigas, UY - Camponogara, Isabel (2006)
This research was developed with the intention of understanding the aquifer dynamics and the underground spring s preservation. In that sense, it was had as main objective to study the natural vulnerability of the Guarani Aquifer System and to analyze physiochemical parameters of the groundwater in the cities of Quaraí - Brazil and Artigas - Uruguay, due to the exploited waters of this aquifer, they be used mainly for human consumption. This way, it was used for the execution of the study, pré-existent data, field research and computer techniques. The methodology used to study the aquifer natural vulnerability leaned on in the DRASTIC Model. To characterize the groundwater, it was made analysis of physiochemical parameters in samples collected in March of 2005. As more relevant result it was verified the relation to the natural vulnerability of the aquifer in the area, that same varied of vulnerable, very vulnerable and extremely vulnerable classes. For the obtained results of the analyses of the physiochemical parameters, we stand out that the waters were classified in 5 types: CaHCO3, CaMgHCO3Cl, MgHCO3, CaMgHCO3 and CaNaHCO3. However, it is evident the importance of the accomplishment of researches of that nature, because the results can be used to manage groundwater hydrics resources in a maintainable way. On the other hand, it is waited that the obtained information and the applied methodologies in this research can subsidize addressed actions to the integrated administration of the groundwater hydrics resources between Brazil and Uruguay, mainly in the plans of use of the water, in agreement with foreseen on its legislation.